2018
DOI: 10.1080/17518423.2018.1476602
|View full text |Cite
|
Sign up to set email alerts
|

Virtual reality training to enhance behavior and cognitive function among children with attention-deficit/hyperactivity disorder: brief report

Abstract: Treadmill-training augmented with virtual-reality is feasible and may be an effective treatment to enhance behavior, cognitive function and dual-tasking in children with ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(38 citation statements)
references
References 27 publications
1
37
0
Order By: Relevance
“…Results showed that the presence of the virtual avatar increased the problem-solving ability of the subjects. These bene ts were also con rmed in the work of Shema-Shiratzky, Brozgol CornejoThumm 33 . Summarizing, avatars showing behaviours that the users feel as familiar 35 can become real tutors, coaches, motivators, mentors, models to emulate 34 .…”
Section: A Theory Developed Bymentioning
confidence: 52%
“…Results showed that the presence of the virtual avatar increased the problem-solving ability of the subjects. These bene ts were also con rmed in the work of Shema-Shiratzky, Brozgol CornejoThumm 33 . Summarizing, avatars showing behaviours that the users feel as familiar 35 can become real tutors, coaches, motivators, mentors, models to emulate 34 .…”
Section: A Theory Developed Bymentioning
confidence: 52%
“…Results showed that the presence of the virtual avatar increased the ability of problem-solving of the subjects. These benefits were also confirmed in the work of Shema-Shiratzky, Brozgol CornejoThumm [33]. Summarizing, avatars can become real tutors, coaches, motivators, mentors, models to emulate [34] they show behaviour which is very similar to that which human beings face daily [35].…”
Section: Introductionmentioning
confidence: 75%
“…Termed ‘serious games’ due to their training purpose rather than for entertainment, these digital games for ADHD can train several cognitive domains [ 34 ]. They can also incorporate biofeedback, virtual reality and augmented reality to facilitate mastery and transfer effect to untrained domains and ultimately, to daily life situations [ 35 – 38 ]. Such digital training has been shown to lead to EEG changes in the prefrontal cortex [ 39 ].…”
Section: Resultsmentioning
confidence: 99%